Edukasi Dermatitis Atopik Terhadap Orangtua/Wali Siswa di TK dan KB Tunas Daud Mataram - Dedianto Hidajat; Dian Puspita Sari; Anak Agung Ayu Niti Wedayani; Pujiarohman Pujiarohman (Jurnal Gema Ngabdi, 2020)
Atopic dermatitis (AD) is a chronic, recurrent skin inflammatory disease that commonly affects children. There is an increasing prevalence of AD in South East Asia and this creates a high economic burden in addition to reducing patients’ and family quality of life. Correct understandings of the disease and its management are very important for family or caregiver of children with AD. Nevertheless, misunderstandings, lack of information and adherence to therapy and poor self-management are the main reasons of dissatisfaction with treatment. Parents often mistook food allergy as the cause of DA and this lead to unnecessary avoidance of certain food. This potentially leads to nutritional problems in children. This educational intervention activity aimed to increase parent and teachers’ knowledge regarding the cause and symptoms of AD, as well as appropriate diagnostic and therapeutic approach for children with AD. This activity was delivered in the form of lecture and discussion, and 75 parents and teachers participated in this event. Almost half of the participants (34 people) had not heard about AD previously. Based on the analysis of pretest (median 5.00) and posttest (median 8.00) results, we found a significant improvement of knowledge on AD among participants (p < 0.01). Pretest scores were associated with participants’ age, while posttest scores were associated with participants’ education level. In conclusion, this educational intervention had been successfully improved participants’ knowledge of AD.